(untitled) (Chemical Engineering Research Bulletin, 2017)
A liquid anionic-zwitterionic surfactant-based aqueous two-phase extraction was developed and applied for the extraction of erythromycin. Erythromycin solubilization from aqueous to reverse micelle phase was studied. Zwitterion SB3-18 surfactant was added to ionic solution of bis(2-ethylhexyl) sulfosuccinate sodium salt (AOT) to form an organic mixed micellar phase. Erythromycin was then added to the mixtures and two clear phases were formed. The parameters affecting erythromycin solubilization including AOT concentration (20.0 ? 120.0 g/L), zwitterion concentration (6.0 ? 16.0 g/L), NaCl concentration (0.0 ? 25.0 g/L) and aqueous pH (6.0 ? 9.0) were investigated via statistical software. Solubilization of erythromycin into mixed reverse micelle could be easily evaluated by the measurement of erythromycin concentration in the organic phase. The results showed that AOT and zwitterion concentration governed the erythromycin solubilization by a factor of 4.562 based on the Pareto chart. Chemical Engineering Research Bulletin 19(2017) 123-128